Mechanism of Valeriana officinalis L. extract improving atherosclerosis by regulating PGC-1α/Sirt3/Epac1 pathway - Yao, Bo; Ma, Jingzhuo; Ran, Qingzhi; Chen, Hengwen; He, Xuanhui (Frontiers in Pharmacology, 2024)
Objective: To investigate the protective effect of the of Valeriana officinalis subsp. officinalis. extract on mitochondrial injury in AS mice and the underlying mechanism.: Firstly, Ultra-High performance liquid chromatography-quadrupole time-offlight mass spectrometer (UPLC / Q-TOF-MS) was proposed to explore the chemical composition of Valeriana officinalis subsp. officinalis extract. ApoE -/-mice were employed for in vivo experiments. The efficacy of Valeriana officinalis subsp. officinalis extract was detected by B-ultrasound, Biochemical, Oil Red O staining, HE staining and Masson staining analysis. The molecular mechanism of Valeriana officinalis subsp. officinalis. extract in regulating mitochondrial energy metabolism for the treatment of atherosclerosis was elucidated after Monitoring System of Vascular Microcirculation in Vivo and transmission electron microscopy. Use the corresponding reagent kit to detect ACTH level, CHRNα1 level and ATP level, and measure the expression levels of PGC-1α, Sirt3, Epac1, Caspase-3, and Caspase-9 through real-time qPCR, and Western blot. Results: A total of 30 metabolites were newly discovered from 2 KYXC using UPLC-MS. The drug had a significant positive effect on the growth of atherosclerotic plaque in mice. It also improved the microcirculation of the heart and mesentery, reduced the levels of CHOL, TG, and VLDL in the serum, and increased the levels of HDL-C to maintain normal lipid metabolism in the body. Additionally, it increased the levels of ATP, improved the ultrastructure of mitochondria to maintain mitochondrial energy metabolism, and increased the levels of T-SOD to combat oxidative stress of the organism. Furthermore, the drug significantly increased the mRNA and protein expression of PGC-1α and Sirt3 in aortic tissue, while decreasing the mRNA and protein expression of Epac1, Caspase-3, and Caspase-9. Conclusion: This study has verified that the extract of Valeriana officinalis subsp. officinalis is highly effective in enhancing atherosclerosis disease. The mechanism is suggested through the PGC-1α/Sirt3/Epac1 signaling pathway, which improves mitochondrial energy metabolism.